Agulhamento seco do músculo masseter: efeito na percepção do zumbido de pacientes com DTM - Miyashiro, Katia Sirikaku [UNIFESP] (2019)
Objective: To evaluate the effect of dry needling of trigger points on the masseter muscle and the effect on tinnitus perception in TMD patients of muscular origin. Method: A double-blind randomized clinical trial was performed. After the otorhinolaryngological evaluation, the screening questionnaire for orofacial pain and temporomandibular dysfunction recommended by the American Academy of Orofacial Pain was applied. Patients who fit the inclusion criteria and agreed to participate in the study had a diagnosis of temporomandibular dysfunction confirmed by the Research Diagnostic Criteria for Temporomandibular Disorders. The sample consisted of 25 participants randomly assigned to the study group (n = 13) and the control group (n = 12). The inclusion criteria were: patients with tinnitus (constant or intermittent) for at least 6 months; modulation of tinnitus in at least one trigger point (active or latent) during bilateral palpation of the masseter muscle, age between 18 and 60 years, patients with normal audiometric thresholds, or mild sensorineural hearing loss. All study participants received guidance and advice on temporomandibular dysfunction. The needling procedure (dry and sham) was performed in 3 sessions. The study group received the dry needling and the control group received the sham (placebo) needle. Participants were evaluated using the Visual Analogue Scale for the intensity of pain and tinnitus and annoyance caused by tinnitus and total Tinnitus Handicap Inventory, both before and at the end of treatment, and at 30, 60 and 90 days after the end of the treatment. Results: After three treatment sessions, in the study group there was an improvement in pain intensities in 84.6% of the participants, and 76.9% showed improvement in tinnitus intensity, discomfort, and reduction in total THI. In the control group, 91.7% of the participants presented improvement in pain intensity, 66.7% had an improvement in tinnitus intensity and a reduction in total THI, and 58.3% reported an improvement in the annoyance caused by tinnitus. After 90 days of treatment completion, in the study group, 84.6% maintained improvement in pain intensity and reduction in THI score, and 69.2% reported improvement in both intensity and distress provoked by tinnitus. In the control group, 75% achieved improvement in pain intensity, 33.2% maintained improvement in tinnitus intensity, and 41.7% maintained improvement in the nuisance and total THI. In the mid-term, there were no differences between the groups in the pain (p = 0.645), intensity (p = 0.073) and distress (p = 0.165) groups and in the total score of the Tinnitus Handicap Inventory only the study group presented improvement (p = 0.041). Conclusion: Dry needling combined with counseling was associated with improvement in the intensity of pain, intensity and discomfort caused by tinnitus and in the reduction of total THI score in the short term. Patients who received dry needling as part of the treatment had a significant improvement in the total score of the Tinnitus Handicap Inventory in the mid-term.